Consent, agreement, communities and holders: the issue of social participation in the field of cultural heritage and the dialogue between the Convention for the Safeguarding of Intangible Heritage and the intangible heritage policy of Brazil (Cadernos de Sociomuseologia, 2021)
This article considers some modes of activation and operationalization of the idea of social participation in the field of intangible cultural heritage. It regards the newest proposal of operating participation established by the UNESCO Convention on Safeguarding Intangible Cultural Heritage and the experience of its implementation in Brazil. By analyzing how the issue of participation was developed through dialogue between the international and national levels, the paper also shows how the emergence of categories of social actors such as “communities” and “bearers” has been consolidated within the mentioned intangible cultural policies.Keywords: social participation; communities; intangible cultural heritage; UNESCO; Brazil